Narrow-linewidth tunable lasers with retro-reflective external cavity - Wang, Ning (2013)
This letter presents the development of a fiber-pigtailed narrow-linewidth tunable laser that utilizes a retro-reflective optical system to construct the external cavity. For wavelength selection, a fixed etalon is employed to provide the International Telecommunication Union (ITU) grid with the 50-GHz spacing and a lead zirconate titanate-actuated tunable filter to select one ITU mode to resonate. The laser device measures a linewidth of 7 kHz, an output power of 14 dBm, a sidemode suppression ratio (SMSR) 55 dB, a tuning range 40 nm, and a response speed ~2 ms. The superior performance well demonstrates the advantages of external cavity construction for the narrow-linewidth tunable lasers and may find applications in the emerging digital coherent communications.